El sentido de las emociones en el Derecho penal - María José Bernuz Benitez (Nuevo Foro Penal, 2013)
This article is a review of the role that emotions should have in law and, more specifically, in the criminal law. It also examines the possible effects it has -or should have- for the criminal law, the admission of emotionally charged penalties and the role that should be played by the rationalization of punishment in such cases.